Bilateral maxillary sinus floor augmentation with tissue-engineered autologous osteoblasts and demineralized freeze-dried bone - Aashish Deshmukh; Rinku Kalra; Shruti Chhadva; Angad Shetye (Wolters Kluwer Medknow Publications, 2015)
The pneumatization of the maxillary sinus often results in a lack of sufficient alveolar bone for implant placement. In the last decades, maxillary sinus lift has become a very popular procedure with predictable results. Sinus floor augmentation procedures are generally carried out using autologous bone grafts, bone substitutes, or composites of bone and bone substitutes. However, the inherent limitations associated with each of these, have directed the attention of investigators to new technologies like bone tissue engineering. Bone marrow stromal cells have been regarded as multi-potent cells residing in bone marrow. These cells can be harvested from a person, multiplied outside his body using bioengineering principles and technologies and later introduced into a tissue defect. We present a case where tissue-engineered autologous osteoblasts were used along with demineralized freeze-dried bone for sinus floor augmentation.